PENGARUH STRUKTUR MODAL DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN INDUSTRI BARANG KONSUMSI 2019-2023 - MALIKA YULIANI; RONAL APRIANTO; ERI TRIHARYATI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2025)
Indonesian companies face significant pressure on of the main challenges is maintaining stable financial performance which is a key determinant of company value. Using the partial least square (PLS)-SEM method through the smartpls program versition 3.0, the population in this study in this study was 133 consumer goods companies listed on the Indonesia stock exchange in 2019-2023. The sampling method used purposive sampling. The result of the study with a t-staistic value of 0.519 and a p-value of 0.604 because the t-statistic value> 1.96 and p-value < 0.05 can be concluded that shows that the capital structure does not affect the value of the company, t-statistic value of 1.180 and p-value 0.238 that the t-statistic value <1.96 and p-value> 0.05 can be concluded that profitability has not significant effect on the value of the company, the t-statistic value of 1.316 and p-value of 0.189. Because the t-statistic value < 1.96 and p-value> 0.05 can be concluded that dividend policy cannot moderate capital structure on the value of the company, the t-statistic value of 2.820 and p-value of 0.005. With a t-statistic value > 1.96 and a p-value < 0.05, it can be concluded that dividend policy can moderate profitability and firm value. The meaning of research is its importance in making invesment decisions and can provide input in determining financial policies.